PERSEPSI TENTANG PENGEMBANGAN KARIR KARYAWAN TSM - MANAHAN P TAMPUBOLON (Jurnal Bisnis dan Akuntansi, 2006)
The objective of this research is to study ithe relationship between, organization culture, job satisfaction, tolerance for conflict, with perception for career development. This research was conducted at Trisakti School of Management at Jakarta with sample selected randomly. The research concludes that there are positive correlation between; 1). Organization culture with perception for career development, 2). Job satisfaction with perception for career development, 3). Tolerance for conflict with perception for career development. Moreover, there is positive correlation between organization culture, job satisfaction, and tolerance for conflict, with perception for career development.